2008
DOI: 10.1007/s10295-008-0397-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the cell surface hydrophobicity and survival of bacteria Zymomonas mobilis after exposures to ethanol, freezing or freeze-drying

Abstract: An inverse linear relationship (P < 0.01) was detected between the cell surface hydrophobicity (CSH) and survival of ethanologenic bacteria Zymomonas mobilis 113S exposed to elevated (2.55 M) ethanol concentration. In the same way, viable cell counts of relatively hydrophobic Z. mobilis were less diminished by growing (0.85-3.40 M) ethanol concentrations as compared to more hydrophobic bacteria. Very similar inverse relationships (P < 0.01) were observed between the CSH of intact Z. mobilis and survival of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
1
5
0
1
Order By: Relevance
“…For example in cell biomass with CSH from 61.2 to 75.1% the total carbohydrate content decreased from 20.93 to 10.50% DW and the protein content increased from 58.99 to 67.45% DW. Similar relationships were detected for bacteria Z. mobilis 113S and reported previously [13]. Observed…”
Section: Resultssupporting
confidence: 91%
“…For example in cell biomass with CSH from 61.2 to 75.1% the total carbohydrate content decreased from 20.93 to 10.50% DW and the protein content increased from 58.99 to 67.45% DW. Similar relationships were detected for bacteria Z. mobilis 113S and reported previously [13]. Observed…”
Section: Resultssupporting
confidence: 91%
“…Benzoic acid was metabolized for cell growth by benzoate metabolism pathway biodegradation. Microorganisms with higher CSH were supposed to have potential superiorities in petroleum bioremediation and endurance stress conditions (Plaza et al 2005;Shakirova et al 2008). Zhang et al (2010) reported the biodegradation of beta-cypermethrin (beta-CP) degrading by two Serratia strains and further investigation found that high hydrophobicity of cells could enhance the degradation of beta-CP.…”
Section: Identification Of Dehp Metabolitesmentioning
confidence: 98%
“…28 Lipopolysaccharides (LPS) form the last outer layer of the cell wall in gram negative proteobacteria 29 and are therefore affected rst when environmental conditions change. Shakirova et al 20 showed a carbohydrate content reduction in LPS fractions of more hydrophobic Z. mobilis cells concomitantly with a proportional decrease of ketodeoxy gluconic acid concentration in corresponding LPS samples. Therefore, it can be concluded that PEG changes the LPS of Z. mobilis, possibly by altering the amounts of LPS constituents.…”
Section: Growth Of Z Mobilismentioning
confidence: 98%
“…16 Several studies have investigated the effect of various environmental conditions and shocking procedures such as freeze-drying, freezing and thawing on the viability and ultra-structure of Z. mobilis. [17][18][19][20] Zikmanis et al 18 studied the effect of different amphiphilic compounds on the hydrophobicity and protein secretion of Z. mobilis. The effect of some surfactants, especially nonionic surfactants of the tween group on Pseudomonas aeruginosa, Escherichia coli, Saccharomyces cerevisiae and Mycobacterium paratuberculosis were examined; the studies mentioned above reected the change of growth and ethanol tolerance of these microorganisms as inuenced by the tested surfactants through the changes of membrane constituents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation